Internal and external successions in family firms: a meta-analysis. Issue 1 (1st October 2020) - Schlömer-Laufen, Nadine; Rauch, Andreas
Abstract : Purpose: Despite much progress in the field of family business research, there is still no unequivocal quantitative evidence on how many family businesses are generally transferred within the family and how many are sold to nonfamily members. Accordingly, the purpose of our paper is to overcome this data problem and to try to get a better estimate of these rates. Design/methodology/approach: To determine a better estimate of intrafamily successions in Germany, we conducted a meta-analysis of 33 samples from 27 studies covering 75, 522 firms facing or having already faced a business transfer. Findings: Our results indicate that 62% of these family firms are (planned to be) transferred to family members. This type of industry strongly determines the mode of succession. However, methodological issues like study quality and sample design also influence estimated succession rates. Practical implications: Policymakers need robust statistics so they can base their actions and economic policies on reliable information. However, in the absence of official statistics – as in the case of family firms handing over their company within or outside the family – information is difficult to generate. Our findings provide a generalizable estimate of prevalence rates, providing German policymakers, and those in other countries when applying these methods, with useful information. Originality/value: This paper suggests that a theory of family firm succession needs to consider more deeply the context in which succession decisions occur. By exploring variables affecting succession rates such as firm size and industry but also methodological issues like sample design and study quality, our analysis also provides a better understanding of central determinants of successions within and outside the family.